A statistical assessment of the ecological dimension of the Romanian economy - Constantin Mitrut (European Regional Science Association (ERSA), 2001)
Starting from the available statistical information this paper proposes an analysis of the ecological dimension of the Romanian economy. Considering the crucial importance of reducing carbon dioxide emissions to diminishing greenhouse effects an econometrical model has been conceived so as to study the correlation between these emissions and their main determinants. Some major difficulties in detailed environmental data collection and constructing long time series have been revealed on this occasion.
Keywords: 330